Effect of Rosemary and Marjoram Extracts on Oxidative Stability of Refined Sunflower Oil - صهيوني, علي; ديمة الدياب (Latakia University Journal -Medical Sciences Series, 2023)
The purpose of this study is to evaluate the effect of rosemary (Rosemarinus officinalis L.) and marjoram extracts (Origanum majorana L.) on thermal stability of sunflower oil. Refined sunflower oil free of additives and supplemented by herbal extracts and butylated hydroxytoluene (BHA) at the concentration of (200 ppm) then subjected to heating in oven at 100 °C for 15, 30, 45, 60 minutes. To track the progress of lipid oxidation: peroxide value (PV), p-anisidine value (p-AV) and TOTOX value were determined. Total phenolic content was determined using Folin-Ciocalteu colorimetric method and can be summarized as following: aqueous rosemary extract > aqueous marjoram extract > ethyl acetate rosemary extract > ethyl acetate marjoram extract > ethanolic rosemary extract > ethanolic marjoram extract. All extracts reduced the oxidation indicator values significantly (p < 0.05). Ethanolic extract of rosemary had the higher antioxidant activity compared to BHA (200 ppm) and other tested extracts during heating period of sunflower oil. Results show that rosemary extracts and marjoram extracts can be used as a natural antioxidant in edible oils.